Loose cigarette purchase and adolescent smoking in Indonesia: a mixed-methods study - Vid Adrison; Dian Kusuma; Gea Melinda; Fariza Zahra Kamilah; Syifa Rizki Amelia; Sofwatun Nida (BMJ Open)
Objectives To investigate the relationship between purchasing loose cigarettes and adolescent smoking habits in Indonesia.Design and setting This study employed a mixed-methods sequential explanatory design. We analysed the secondary data from a national survey, the 2019 Global Youth Tobacco Survey, using multivariable logistic regression models to examine the association between loose cigarette purchase and smoking frequency and intensity and nicotine dependence. Based on the quantitative findings, we arranged focus group discussions (FGDs) in junior and senior high schools located in South Jakarta, Indonesia. The qualitative data were analysed using thematic analysis with an inductive approach to explore experiences in purchasing loose cigarettes and how it affected their smoking initiation and current cigarette consumption.Participants For quantitative study, we included 785 samples after excluding the non-current smokers and those who had missing responses. For qualitative study, a total of 49 eligible students who met inclusion criteria (ever or current smokers, buying loose cigarettes and living with parents) and agreed to participate in FGD were later divided into 12 FGD groups.Results Most students who smoked in the past 30 days are male (95%). More than half of the students (68%) reported buying loose cigarettes in the past 30 days, including 36% who smoked 1–2 days in a month and 34% who usually consumed one cigarette a day. One-third of the students had nicotine dependence (30%), with an average smoking duration of 3 years. Purchasing loose cigarettes in the past 30 days was significantly correlated with smoking for <20 days in the past month (adjusted OR (AOR)=1.56; 95% CI=1.17 to 2.07), consuming ≤5 sticks per day (AOR=2.15; 95% CI=1.54 to 3.00) and having lower nicotine dependence (AOR=1.55; 95% CI=1.08 to 2.22). Our qualitative findings further reported that affordability and accessibility were the main reasons that encouraged current student smokers to opt for loose cigarettes over other types of cigarettes (packs, cartons or rolled tobacco). Students reported the extensive selling of loose cigarettes and such a situation persuaded them to buy tobacco products more frequently, thus spending at least half of their weekly allowance on tobacco products, ranging from 30 000 to 200 000 Indonesian rupiah or equivalent to US$2–13 per week. Finally, our study highlighted that only a few students in this study either had to show their identity card or were denied when purchasing loose cigarettes in informal retailers.Conclusion Our study demonstrates that students purchasing loose cigarettes is significantly associated with non-daily smoking, consuming five or fewer sticks per day, and lower addiction which could be interpreted as smokers in the experimental phase. They possessed a higher risk of becoming regular smokers. Our qualitative findings supported the quantitative study by shedding light on the role of loose cigarettes in smoking initiation and continuation among young people. In this case, we supported the notion of prohibiting loose cigarette sales in the country in order to reduce smoking uptake and tobacco consumption among the younger generation.